Regenerasi Kepemimpinan Multiplikatif di Era Digital: Implikasi bagi Kepemimpinan Kristen Kontemporer - Widjaja, Rita; Simondinata, Gunawan; Leoni, Stella; Simanjuntak, Manlian Ronald Adventus (Jurnal Riset Rumpun Agama dan Filsafat, 2026)
The rise of the digital age has brought significant changes to leadership dynamics and leadership development patterns within the context of Christian ministry. This paper addresses the critical issue of leadership succession failure, which is driven by a generational gap between senior leaders and young leaders-in-training, as well as the underutilization of technology in the mentoring process. Using a descriptive qualitative approach through literature review, state-of-the-art analysis, and theological synthesis, this study assesses the relevance and effectiveness of the multiplicative leadership model as a solution to the leadership succession problem. The analysis reveals that multiplicative leadership—which emphasizes discipleship, intensive mentoring, delegation of responsibility, and intergenerational collaboration—can bridge the generational gap while accelerating the multiplication of leaders in the digital age. The integration of digital technologies, such as virtual mentoring, digital training modules, and collaborative media, has proven capable of expanding the impact of the leadership development process and enhancing relational closeness between generations. This paper concludes that the multiplicative leadership model is a strategic and theological approach aligned with the biblical mandate to produce leaders capable of developing other leaders, and is relevant for addressing the challenges of contemporary Christian leadership.